Functional Living in Older Adults With Type 2 Diabetes: Executive Functioning, Dual Task Performance, and the Impact on Postural Stability and Motor Control. (August 2014) - Smith, Michael A.; Else, Jane E.; Paul, Lorna; Foster, Jonathan K.; Walker, Mark; Wesnes, Keith A.; Riby, Leigh M.
Objective: Older adults with type 2 diabetes mellitus (DM2) experience accelerated age-related decline in some domains of cognition. The present study sought to investigate executive functioning and dual tasking capacities in this group.Method: Older adults with DM2 and age-matched controls completed self-report measures assessing everyday activities, a comprehensive cognitive battery and more specific tasks assessing executive functioning, dual tasking, postural stability, and motor control.Results: Executive abilities were particularly compromised in the participants with DM2. Furthermore, the DM2 group exhibited reduced postural stability under dual task conditions.Discussion: These findings suggest that deficits in more complex cognitive activities underlie the decline in everyday function in DM2.